Identification of two novel mammographic density loci at 6Q25.1. Issue 1 (December 2015) - Brand, Judith; Li, Jingmei; Humphreys, Keith; Karlsson, Robert; Eriksson, Mikael; Ivansson, Emma; Hall, Per; Czene, Kamila
Abstract Introduction Mammographic density (MD) is a strong heritable and intermediate phenotype for breast cancer, but much of its genetic variation remains unexplained. We performed a large-scale genetic association study including 8, 419 women of European ancestry to identify MD loci. Methods Participants of three Swedish studies were genotyped on a custom Illumina iSelect genotyping array and percent and absolute mammographic density were ascertained using semiautomated and fully automated methods from film and digital mammograms. Linear regression analysis was used to test for SNP-MD associations, adjusting for age, body mass index, menopausal status and six principal components. Meta-analyses were performed by combiningP values taking sample size, study-specific inflation factor and direction of effect into account. Results Genome-wide significant associations were observed for two previously identified loci:ZNF365 (rs10995194, P = 2.3 × 10−8 for percent MD andP = 8.7 × 10−9 for absolute MD) andAREG (rs10034692, P = 6.7 × 10−9 for absolute MD). In addition, we found evidence of association for two variants at 6q25.1, both of which are known breast cancer susceptibility loci: rs9485370 in theTAB2 gene (P = 4.8 × 10−9 for percent MD andP = 2.5 × 10−8 for absolute MD) and rs60705924 in theCCDC170 /ESR1 region (P = 2.2 × 10−8 for absolute MD). Both regions have been implicated in estrogen receptor signaling with TAB2 being a potential regulator of tamoxifen response. Conclusions We identified two novel MD loci at 6q25.1. These findings underscore the importance of 6q25.1 as a susceptibility region and provide more insight into the mechanisms through which MD influences breast cancer risk.